RNA/DNA ratios in American glass eels (Anguilla rostrata): evidence for latitudinal variation in physiological status and constraints to oceanic migration? - Laflamme, Simon (Blackwell Publishing Ltd, 2012)
During their larval leptocephalus phase, newly hatched American eels undergo an extensive oceanic migration from the Sargasso Sea toward coastal and freshwater habitats. Their subsequent metamorphosis into glass eel is accompanied by drastic morphological and physiological changes preceding settlement over a wide geographic range. The main objective of this study was to compare RNA/DNA ratios and condition factor among glass eels in order to test the null hypothesis of no difference in physiological status and metabolic activity of glass eels at the outcome of their oceanic migration. This was achieved by analyzing glass eel samples collected at the mouth of 17 tributaries covering a latitudinal gradient across the species distribution range from Florida to Gaspésie (Québec). Our main observations were (i) a latitudinal increase in mean total length; (ii) a latitudinal variation in mean RNA/DNA ratios, which was best explained by a quadratic model reaching its minimum in the central range of sampling locations; and (iii) a latitudinal variation in Fulton's condition factor, which was best explained by a quadratic model reaching its maximum in the central range of sampling locations. Below we discuss the possible links between latitudinal variation in glass eel physiological status and variable energetic and environmental constraints to oceanic migration as a function of latitudinal distribution.